LAW DOCUMENTS IN THE TEXTS EUPHEMISM: LEGAL LANGUAGE AND SOCIAL CULTURE HARMONY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the phenomenon of euphemization used in the texts of legal documents. The role of euphemisms in ensuring the formality, neutrality, and social impact of legal texts is examined. In addition, the purpose, types, and features of euphemization in legal discourse are explained on the basis of examples.